(untitled) (Global Journal of Human-Social Science, 2021)
This research article presents the various sociocultural perspectives generated as a result of the influence of major entertainment figures such as J Balvin Rihanna Beyonce and the kpop group of the moment BTS through case studies on the aforementioned characters it is possible to conclude the various sociocultural scenarios It also presents the massive diffusion of fashion trends through the digital world and how the use of different web platforms to acquire the various products has grown due to the current health situation of the Covid-19 pandemic impacting the fashion industries and their economic growth